Cognitive effects of acute aerobic exercise: Exploring the influence of exercise duration, exhaustion, task complexity and expectancies in endurance-trained individuals - McCartney, D.; Desbrow, B.; Irwin, C. (Journal of Sports Sciences, 2021)
The cognitive effects of acute aerobic exercise were investigated in endurance-trained individuals. On two occasions, 21 cyclists; 11 male (VO2max: 57 ± 9 mL·kg-1·min-1) and 10 female (VO2max: 51 ± 9 mL·kg-1·min-1), completed 45 min of fixed, moderate-intensity (discontinuous) cycling followed by an incremental ride to exhaustion. Cognitive function was assessed at Baseline, after 15 and 45 min of exercise (15EX and 45EX) and at Exhaustion using a 4-Choice Reaction Time (CRT) test and the Stroop test (Incongruent and Congruent Reaction Time [RT]). A sham capsule was administered on one occasion to determine whether the cognitive response to exercise was robust to the influence of a placebo. CRT, Congruent RT and Incongruent RT decreased (improved) at 15EX, 45EX and Exhaustion compared to Baseline (p`s<0.005). While CRT and Congruent RT were faster at 45EX than 15EX (p`s<0.020), Incongruent RT was not (p= 1.000). The sham treatment did not affect cognition. When performed at a moderate-intensity, longer duration exercise (up to 45 min) may improve cognition to a greater extent than shorter duration exercise; however, the magnitude of improvement appears to decrease with increasing task complexity. HI/EE performed following a sustained bout of dehydrating activity may not impair cognition.